Early impact of COVID-19 on sport and physical activity participation. (AusPlay, 2020)
The Australian Government is working to improve the health and wellbeing of Australians and build stronger communities through participation and engagement with sport. However, the ability for Australians to be active in their communities has been interrupted since COVID-19 was first confirmed in Australia in late January 2020. In particular, the coronavirus pandemic has had a significant impact on organised sport as these gatherings were put on hold to adhere to health advice. The Australian Government, through Sport Australia and the Australian Institute of Sport, has helped sporting organisations adapt to a COVID-19 environment and a safe return to sport when possible. We`ve also kept in touch with the Australian community during the pandemic to understand how their activity behaviours have changed and how they`re feeling about getting involved in sport. As such, most of the data in this report is sourced from two surveys of the Australian community that are funded and led by Sport Australia: - AusPlay - the only publicly funded national population survey of adults aged 15 or over and children 0-14 about their participation in sport and physical activity; and - Community Perceptions Monitor - a monthly survey of Australian adults aged 18 or over on a range of topics related to sport and physical activity. - Specific questions about COVID-19 were added to both surveys from April 2020.